2014
DOI: 10.1001/jamadermatol.2013.8354
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies and Disease Activity in Patients With Discoid Lupus Erythematosus

Abstract: Serologic markers mirroring disease activity in patients with discoid lupus erythematosus (DLE) are unknown. Identifying them would help predict disease course, guide treatment, and clarify the etiology of DLE. Because autoantibodies have been associated with systemic lupus erythematosus (SLE) disease activity, 1 we investigated associations between autoantibodies and disease activity measures in patients with DLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…The correlation of anti‐U1‐RNP antibodies with photosensitivity and the presence of DLE in SLE patients have been described before . Recently, a correlation between disease activity and level of anti‐RNP IgG was reported . Taking into consideration that anti‐ds‐DNA antibodies correlate moderately with disease activity, especially in renal involvement, our results could also implicate that patient with SLE and CLE may have a higher disease activity.…”
Section: Discussionsupporting
confidence: 78%
“…The correlation of anti‐U1‐RNP antibodies with photosensitivity and the presence of DLE in SLE patients have been described before . Recently, a correlation between disease activity and level of anti‐RNP IgG was reported . Taking into consideration that anti‐ds‐DNA antibodies correlate moderately with disease activity, especially in renal involvement, our results could also implicate that patient with SLE and CLE may have a higher disease activity.…”
Section: Discussionsupporting
confidence: 78%
“…Serological studies are also frequently positive; however, antinuclear antibody is less sensitive in cases of isolated DLE than in cases of DLE with concomitant systemic involvement. 6 In cases where LPP and DLE are difficult to distinguish, CD123 immunohistochemical staining for plasmacytoid dendritic cells (PDC) may be helpful. The infiltrate of DLE tends to have >50% PDCs in the reticular dermis 7 with clustering of PDCs, usually >10.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that multiple correlations of ANA, anti‐dsDNA, anti‐RNP and anti‐ssDNA IgG with systemic disease activity measures in all DLE, DLE+/ANA+, and DLE+/SLE+ patients. Thus, they highlighted associations of ANA, anti‐dsDNA, anti‐RNP, and anti‐ssDNA IgG with disease activity in DLE patients 18 …”
Section: Discussionmentioning
confidence: 99%